Antianginal efficacy of exercise training: a comparison with beta blockade. Issue 1 (July 1990) - Todd, I C; Ballantyne, D
Abstract : Forty men with chronic stable angina and no prior myocardial infarction were studied. Exercise tolerance testing was carried out off treatment and after beta blockade. beta Blockers were stopped and the patients were randomised to a control group and a study group of patients who undertook a one year high intensity training programme. The groups were then restudied. Submaximum heart rate was reduced by 13 beats per minute by training and by 23 beats per minute by atenolol. Training increased the maximum heart rate by 10 beats per minute and atenolol reduced it by 29 beats per minute. The double produce ST threshold was increased from 183 to 205 by training but reduced to 143 by atenolol. Maximum ST depression was similarly reduced by both training and atenolol. As a result of the effects on maximum heart rate, training produced a greater improvement in exercise tolerance than atenolol with a treadmill time increased from 741 seconds to 1272 seconds with training compared with 974 seconds with atenolol. Other variables were similarly affected. Thus the antianginal efficacy of exercise training is as good as that achieved by beta blockade and represents an alternative to such treatment.